The Findings of Mycobacterium Leprae DNA Existence in the Air as an Indication of Leprosy Transmission from Respiratory System - Qotrunada Alam Cendaki (JURNAL KESEHATAN LINGKUNGAN, 2018)
There are transmisions source in Infectious Leprosy Hospital Kediri from leprosy patients that can contaminate air with leprosy bacillus. There are also the risk groups, such as medical and non-medical staff, and visitors who contact with the environment. This study was to describe the existence of Mycobacterium leprae DNA in the air at nursing rooms Hospital Infections leprosy Kediri. The method was observational descriptive with object were the entire room of hospital treatment infections leprosy Kediri which consisted of 6 inpatient rooms and 4 outpatient rooms. The variable in this research was existence of Mycobacterium leprae DNA by PCR (Polymerase Chain Reaction) technique. The result showed that leprosy DNA found in nursing room that indicated there was other factors that supporting Mycobacterium leprae in the air. It can be concluded that air can be the temporary potential factors of disease transmission. It's suggested to conduct in positive of Mycobacterium leprae DNA at indoor. So that indoor air is clean and healthy.